Study of sociodemographic correlates, anxiety, and depression among opioid dependents admitted in treatment centres in Sikkim, India - Sharma, Bishnu (Open J Psychiatry Allied Sci, 2019)
BACKGROUND: People with opioid use disorder have significant anxiety and depression which can be because of neuroplastic changes due to use of opioid or because of use as a self-medication to relieve depression and anxiety. During the last one decade, opioid use has reached an alarming proportion in Sikkim, India; but, any research related to anxiety and depression among opioid users has not been done. AIMS: To assess for depression and anxiety disorders among the opioid dependence syndrome (ODS) participants and its severity, and to find the association with the sociodemographic characteristics. METHOD: One hundred participants from three different drug detoxification and rehabilitation centres who were diagnosed with ODS as per the ICD-10, Diagnostic Criteria for Research were assessed cross-sectionally with the Addiction Severity Index to find out the substances abused and psychiatric morbidity. Anxiety, depression, and mania were graded with the Hamilton rating scales for anxiety and depression, and the Young Mania Rating Scale. RESULTS: Mean age of participants was 29.6 (±6.24) years. Ninety six per cent were males. Most of the participants were using multiple opioid preparations. Thirty four per cent were using dextropropoxyphene containing pain killer followed by six per cent using codeine containing cough syrup. Eighty two per cent had depression; however, only 13% were found to have severe depression. Fifty six per cent had anxiety and six per cent were found to have mania. Most of the participants with ODS were single, attended at least secondary education, from urban locality, and were from high socioeconomic status. CONCLUSION: anxiety and depression are highly prevalent among ODS people. Treatment should not be limited to management of ODS but also the comorbid psychiatric illness.